Understanding the Role of the Government to Help Building the Opportunities to Financing "Seed" and "Start-Up" Projects by PE/VC - Jabłoński, Sebastian; Waszkiewicz, Maciej (Zrozumienie roli, jaką odgrywa rząd w stwarzaniu okazji do finansowania projektów typu "seed" i "start-up" przez fundusze typu PE/VC, 2009)
This paper analyzes factors that influence the development of private equity markets at the seed and start-up stage. The authors want to show solutions of the venture capital and angel capital shames that could be potentially considered in Central & Eastern Europe and be developed to facilitate business growth and economic development giving opportunities to access capital. These examples should allow and enable small and new startup businesses to access investment funds and providing incentives for innovation and entrepreneur-ship. The study focuses on evaluating the process to seek financing for start-up or seed capital, examining the significance of such factors including the methods and solution presenting examples of business schemes that help to secure alternative and sourcing funds to raising money which reflects the structure, cost of capital and risk factor associated with that. In the following paper we would like to introduce basic concepts to financing projects with seed and start-up capital. We will discuss some business constrains and strategic decisions to be made by the PE/VC and the entrepreneurs. We will give examples how US Government sponsored project have been operating and describe their main characteristics and business constrains. Moreover, we will give guidelines to show examples of models/schemes for entrepreneurs and small and medium companies to participate in obtaining financing for start-up and seed capital in quasi--private and government sponsored initiatives. (fragment of text)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 48, s. 347-359